PENGARUH BRAND AWARENESS DAN BRAND TRUST TERHADAP KEPUTUSAN PEMBELIAN PRODUK ORIFLAME - RAHAYUSIH W, SRI (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
Oriflame is a company that produce cosmetics from Sweden. Since 1987, Oriflame entrance Indonesian market. In 2013, Oriflame has top brand award and became sponsor of a talent audition in Indonesia. That is the first time of Oriflame publish their product to citizen. This study aims to determine and analyze the effect of brand awareness and brand trust, simultaneously, towards purchase decision and to investigate and analyze the variable which has a dominant influence. This research is a causal research. Criteria for selection of sampling in this study are Oriflame’s consument that use Oriflame’s products within two month. The amount of sample for this study is 107 respondent. The results showed that there simultaneous effect of 57.5% between the two variable, the brand awareness (X1) and brand trust (X2) against purchase decision while the remaining 42.5% are influenced by other variables outside variables used in this study. Brand trust variable (X2) are the dominant variables affecting purchase decision. Further research is suggested to link the acceptance of purchase decision with other variables. Keywords: Brand Awareness, Brand Trust, Purchase Desicion, Cosmetics Product